Acts of Unsettling: An Immersive Adaptation of Berger and Mohr’s A Seventh Man - Frances Babbage; Michael Pinchbeck (Arts, 2023)
This article examines Michael Pinchbeck and Ollie Smith’s theatrical adaptation of A Seventh Man, the 1975 book by John Berger and photographer Jean Mohr studying the experience of migrant workers in Europe. Pinchbeck and Smith’s 2020 adaptation uses immersive performance strategies in dialogue with a multi-voiced, cross-disciplinary publication that itself aims to produce an immersive or ‘animated’ reader engagement. In this article, Babbage and Pinchbeck present source text and performance as examples of practice-as-research, referencing Nelson’s paradigm that establishes different modes of knowledge and points of connection- and dissension-between them. They discuss the book’s cross-disciplinarity and the attempt to reflect this in a new creative context that is spatiotemporal, embodied, social, visual, verbal and aural. The article’s theoretical context draws on writing by Barthes, Berger, Said and Sontag, applying Barthes’ notion of the studium and the punctum to reflect on the dramaturgical rendering of the source text’s ‘interruptive shocks’. Babbage and Pinchbeck argue that, in book and performance, the juxtaposition of different formal languages elicits an encounter with the material that is productively ‘unsettling’.